Illumination of the Problem of Communication of Mentally Retarded Children in Pedagogical, Psychological, and Methodological Literature - Anvarova Dilfuza Akramjanovna (International Journal on Integrated Education, 2022)
In general psychology, speech is studied as a weapon of thinking and a means of communication. In ontogenesis and phyloginesis, speech is initially manifested as a means of communication, later acquiring the properties of weapons, through which a person thinks and expresses his thoughts. About the connection of thinking, language and speech L.S.Vygotsky, A.G.Spirkins have a lot of interesting work. Interesting information in a general way, which is called the development of children's speech, is S. L. Rubinstein and D. V. Elkonin is brought to work.